МАТЕМАТИЧНА МОДЕЛЬ ТРАНСФОРМАТОРА СТРУМУ НА ОСНОВІ ТЕОРІЇ ФЕРОМАГНІТНОГО ГІСТЕРЕЗИСУ ДЖАЙЛСА-АТЕРТОНА - Стогній, Б.С.; Сопель, М.Ф.; Паньків, В.І.; Танкевич, Є.М. (Інститут електродинаміки НАН України, Київ, 2016)
This paper deals with a brief description and the basic equations of the Jiles-Atherton theory of ferromagnetic hysteresis, and information about its application in world practice to construct a mathematical model of the current transformer, calculations and research of electromagnetic processes in these devices. Improving of mathematical model of current transformer based on the Jiles-Atherton theory have been proposed and justified, by the way of describing it anhysteretic magnetization curve by second order fractional rational function instead modified Langevin function. According to the developed model of current transformer, transient currents of TFKN-330 type of current transformer with different steel grades of magnetic cores and with different ways of describing its anhysteretic magnetization curve have been calculated and their comparative analysis have been made. Briefly examined the possibility of using optimization genetic algorithm of differential evolution to determine the parameters of proposed model. References 11, figures 3.